Extension of the CJP model to mixed mode I and mode II - C. J. Christopher; G. Laboviciute; M. N. James (Fracture and Structural Integrity)
The present authors have previously proposed a novel ‘plastic inclusion’ approach for dealing with the local plasticity which occurs at the tip of a growing fatigue crack. This meso-scale model provides a modified set of crack tip stress intensity factors that include the magnitude of plastic wake-induced crack tip shielding and which have the potential to help resolve some long-standing controversies associated with plasticity-induced closure. The present work extends the CJP model to deal with the case of mixed Mode I and Mode II loading and thus opens up enhanced possibilities for testing it on inclined cracks in metallic specimens. This extension requires the addition of only one new force parameter to the model, i.e. an anti-symmetric shear force on either side of the crack.